Ultrathin Nanocrystalline Magnetic Wires - Horia Chiriac; Nicoleta Lupu; George Stoian; Gabriel Ababei; Sorin Corodeanu; Tibor-Adrian Óvári (Crystals, 2017)
The magnetic characteristics of FINEMET type glass-coated nanowires and submicron wires are investigated by taking into account the structural evolution induced by specific annealing all the way from a fully amorphous state to a nanocrystalline structure. The differences between the magnetic properties of these ultrathin wires and those of the thicker glass-coated microwires and “conventional” wires with similar structures have been emphasized and explained phenomenologically. The domain wall propagation in these novel nanowires and submicron wires, featuring a combination between an amorphous and a crystalline structure, has also been studied, given the recent interest in the preparation and investigation of new materials suitable for the development of domain wall logic applications.